A One‐Step Imaging Assay to Monitor Cell Cycle State and Apoptosis in Mammalian Cells. Issue 1 (14th March 2014) - Tang, Yangzhong
Abstract: High‐content screening (HCS; fluorescence microscopy with multiple markers followed by automated image analysis) is gaining popularity in drug discovery due to the rich information it reveals about drug responses. It is particularly useful in studying anti‐mitotic drug responses since mitotic arrest provides an activity biomarker. One conventional way to probe mitotic arrest and downstream apoptosis response is to use mitosis‐ and apoptosis‐specific antibodies in cell‐based imaging assays. However, weakly attached cells, especially dead cells, are mostly washed out during antibody labeling steps. Here, we report a rapid and convenient one‐step cell‐imaging assay that accurately measures cell‐cycle state and apoptosis in mammalian cells. The assay uses three fluorescent dyes to stain living cells, involves no wash, and is fixable after live‐cell labeling. Compared to the antibody‐based method, this assay is quicker, more cost‐effective, and yields more accurate dose‐response results. Curr. Protoc. Chem. Biol . 6:1‐5. © 2014 by John Wiley & Sons, Inc.